BAU MULUT (HALITOSIS - Ni Ketut Ratmini (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2017)
Bad breath (halitosis) ia a problem that concern almost everyone. Bad breath is not uncommon to distance the owner of the association in his neighborhood. Halitosis is a term used to describe unpleasant breath odor emitted when breathing (http://wikipedia.org). Halitosis is estimated about 50%-65% of the population (http://indrax.wordpress.com). The main cause of halitosis is bacteria and VSC’s. Ninety percent of patients had halitosis from the mouth causes such as as poor oral hygiene, periodontal disease, a layer on the surface tongue, impacted food, dirty dentures, mouth cancer, and sore throat (The California Breath Clinic).Several method for measuring halitosis, as follows: organoleptic test, chromatogaraphy gas. halimeter, Bana testing, and chemiluminescence (http://www.animated-teeth.com).Prof. Mel Rosenberg. Ph.D from the Faculty of Dentistry, University of Tel Aviv (citet Chudahman Manan), recommends halitosis prevention by: 1)consult to the dentist regularly. 2)clean between teeth with dental floss, choose a neutral unscented. Check the smell. Clean again if smell. 3)brush your teeth and gums clean regularly. 4)a lot of dringking. 5)sugar free chewing gum for 1-2 minutes, especially if the mouth feels dry. 6)rinse and brush your teeth after eating or drinking milk product, fish, and meat. 7)ask your dentist which mouthwash clinically proven its effectiveness in combating bad breath. Its best to use it just before sleep at night. 8)eat fresh and has fibers vegetables. 9)do not smoke because it heightens the risk of bad breath. 10)if you wear dentures, at night soak dentures in antiseptic solution, unless you forbid dentist.The conclusion is: halitosis or bad breath can develop all the people. The main source of halitosis is in the mouth, that is the volatile sulphur compounds (VSC’s). This compounds is produced from decomposition of protein by anaerobic bacteria.